Crystalline Coating and Its Influence on the Water Transport in Concrete - Pavel Reiterman; Jiri Pazderka (Advances in Civil Engineering)
The presented paper deals with an experimental study of the efficiency of surface coating treatment based on secondary crystallization as an additional protection of the subsurface concrete structure loaded by moisture or ground water pressure. The aim of the experimental program was the evaluation of the depth impact of the crystalline coating and the assessment of the reliability of construction joints performed on models simulating real conditions of the concrete structure. The evolution of the secondary crystallizing process was monitored using the water absorption test carried out at different depths of the samples. The coefficient of adsorption decreased to 60% of the reference mixture for a surface layer of up to 40 mm at 28 days and to 50% at 180 days after the coating’s application. Furthermore, the electrical resistivity method was applied with respect to the nature of measurement and the low accessibility of real subsurface concrete structures. The results of moisture measurement at a depth of 180–190 mm from the surface treated with a crystalline coating showed an essential decrease in moisture content percentage in comparison with untreated specimens (measured 125 days after the coating’s application).